2013
DOI: 10.1155/2013/576258
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Self-Compassion in Generalized Anxiety Disorder: Examining Predictors of Disability

Abstract: Generalized anxiety disorder (GAD) is a condition characterized by worry and physiological arousal symptoms that causes significant disabilities in patients' lives. In order to improve psychotherapeutic interventions, a careful characterization of the deficiencies of this population as well as factors that ameliorate disability is crucial. Variables that have not traditionally been the focus of research should be considered, such as trait mindfulness and self-compassion. We investigated whether GAD patients wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Raes () also found that rumination and worry were partial mediators in the self‐compassion—anxiety relationship. In a similar vein, Hoge et al () found that self‐compassion was a significant negative predictor of worry among individuals with GAD. In addition, self‐compassion has been found to inversely predict emotional avoidance in community samples (Sydenham et al, ) and behavioural avoidance in outpatient clinical samples (Krieger et al, ).…”
Section: Self‐compassion and Cognitive Emotion Regulationmentioning
confidence: 78%
See 2 more Smart Citations
“…Raes () also found that rumination and worry were partial mediators in the self‐compassion—anxiety relationship. In a similar vein, Hoge et al () found that self‐compassion was a significant negative predictor of worry among individuals with GAD. In addition, self‐compassion has been found to inversely predict emotional avoidance in community samples (Sydenham et al, ) and behavioural avoidance in outpatient clinical samples (Krieger et al, ).…”
Section: Self‐compassion and Cognitive Emotion Regulationmentioning
confidence: 78%
“…In support of self‐compassion as a buffer against depressive symptomatology, their results demonstrated that self‐compassion significantly predicted later depressive symptoms and the presence of a major depressive episode over time; in contrast, symptoms of depression did not predict self‐compassion over time. In addition, research on anxiety symptomatology has found that self‐compassion is inversely associated with symptom severity in GAD (Roemer et al, ) and obsessive–compulsive disorder (Wetterneck, Lee, Smith, & Hart, ), while individuals with GAD and SAD report significantly lower self‐compassion than healthy controls (Hoge et al, ; Werner et al, ).…”
Section: Self‐compassion and Symptoms Of Depression And Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of self-compassion have been associated with lower levels of catastrophizing, avoidance, and rumination in chronic pain patients who were presented with vignettes involving a violation of social contract and have been found to predict affect, pain disability, and pain catastrophizing in obese patients with chronic pain [114, 115]. The relationships between self-compassion, anxiety, and disability have been explored in individuals with Generalized Anxiety Disorder; these individuals display lower levels of self-compassion and mindfulness than healthy stressed controls and mindfulness was a better predictor of disability than actual anxiety symptoms, drawing potential protective effects of mindfulness on disability in individuals with chronic worry and physiological symptoms [116]. The relationship between self-compassion and anxiety should be further elucidated and it may be useful to examine the relationships between the subscales of the SCS to better understand which components of self-compassion are most helpful in mediating changes in anxiety in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with people with Generalized Anxiety Disorder (GAD) it was shown that GAD patients reported lower mindfulness and self-compassion levels and higher levels of worry and anxiety (Hoge et al, 2013). According to another Relative to TAU, CFT was associated with greater observed clinical improvement (p < 0.001) and significant increases in compassion (p = 0.015) of large magnitude.…”
Section: Self-compassion and Anxiety Disordersmentioning
confidence: 99%